Adaptive Changes in the Posterior Pharyngeal Wall Following Large Retraction of Incisors During Comprehensive Orthodontic Treatment - Ashok Kumar Jena; Venkatachalapathy Anusuya; Jitendra Sharan (Turkish Journal of Orthodontics, 2022)

(untitled)
Objective:To evaluate the effects of large retraction of incisors on the adaptive changes in the posterior pharyngeal wall and soft palate during comprehensive orthodontic treatment.Methods:Twenty-seven females with Class I mild crowding or spacing who required non-extraction treatment (group I) and 34 females with Class I bimaxillary dentoalveolar protrusion who required all first premolars extraction for the retraction of their incisors (group II) were included in the study. The effects of non-extraction and incisor retraction following all first premolars extraction orthodontic treatment on the sagittal dimensions of pharyngeal airway passage and posterior pharyngeal wall thickness were evaluated from pre- and post-treatment cephalograms.Results:The dimensions of pharyngeal airway passage were comparable among the groups. The length of the soft palate increased (P < .01) and the thickness of the soft palate decreased (P < .01) following retraction of incisors, and the difference between the groups was significant (P < .05). The posterior pharyngeal wall thickness was reduced significantly at PPWT2 (P < .05), PPWT3 (P < .001), PPWT4 (P < .001), PPWT5 (P < .001), and PPWT6 (P < .01) regions following retraction of the incisors, and the difference between the groups was statistically highly significant.Conclusions:The large retraction of incisors during comprehensive orthodontic treatment in Class I bimaxillary dentoalveolar protrusion malocclusion subjects did not affect the sagittal dimensions of pharyngeal airway passage, but the thickness of the posterior pharyngeal wall reduced significantly as an adaptation to maintain the patency of the upper airway.